Precipitating and Relieving Factors of Migraine in Adults - Amin, Md Nurul; Alim, Md Abdul; Asaduzzaman, Md (Ibrahim Cardiac Medical Journal, 2013)
DOI: http://dx.doi.org/10.3329/icmj.v2i1.17382 Ibrahim Cardiac Med J 2012; 2(1): 12-16